Concepções de educação dos docentes gestores do Instituto Federal de Educação, Ciência e Tecnologia de Mato Grosso – IFMT – campus Rondonópolis - Magnabosco, Osmar Antônio (2016)
Quality education is a constant theme in the daily lives of Brazilians, by its lack proclaimed by media, analysts, governments, professionals of multiple areas and common people. It's a recommended solution for most problems of the country. The difficulty that is needed is to know about what education is being discussed, in view of the diversity of understanding about the subject. This issue affects directly the educational institutions. Deepen in the understanding of this dynamic in an institution with a few years of operation, whose members presents diversity of origin, age, life experience, human and academic background and professional expectation, is the reason of this work. For this, it intends to identify the conceptions of education of managers teachers of the Federal Institute of Education, Science and Technology Mato Grosso – IFMT – Campus Rondonópolis. The origin of this proposal is in the observations of the researcher about conflicts concerning objectives and methods of education and teaching and about the disparity of approaches, by teachers, on topics such as learning difficulties, indiscipline and lack of motivation, on the part of students. From the understanding that it was necessary to seek the ultimate source for the observed discrepancies, it has become necessary to understand the generator and the justifier thought of all actions. To achieve this purpose, research was conducted with a qualitative approach, using initially bibliographical research, to understand the thinking of authors such as Freire, Dewey and Severino, beyond the Educational Institution proposal manifested in its Institutional Development Plan - PDI. Then proceeded to the analysis and interpretation of narratives of personal and professional itineraries of the subjects and also of the answers they gave to questionnaire with open questions. The investigated subjects play the dual role of teachers and managers of the Institution. The results showed significant differences in the conception of education and its related topics, such as teaching, learning, school function and knowledge, that result from academic formation of subjects, some belonging to technical areas and other to humanities areas. The first ones are closer to the concept of banking education, of Freire, with the predominance of knowledge transmission idea. They attach to the family the function to educate and to the school the function to teach. They have a positive view about the paths taken by the Institution. The second group advocates a transformative education, both of the individual and the society. For them, to form critical citizens, producers of knowledge, is a function of education. They have a critical perception of the paths followed by the institution. In terms of engagement, commitment to the students, though in different ways, the groups are equal. The differences found in this study highlight the need for debates and ongoing dialogue, promotion of activities of integrative character that emphasize team spirit. And above all, continuing education programs for teachers will bring closer the visions, reducing disparities. It is an educational opportunity to an educating institution. This research is linked to the Program of Graduate Studies in Education, of the Institute of Human and Social Sciences, of the Rondonópolis University Campus, of the Federal University of Mato Grosso, in the line of Teacher Formation and Educational Public Policy.